PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN KONSUMEN MEMBELI KENDARAAN RODA DUA MEREK YAMAHA DI PD. TURBO MOTOR PONTIANAK - Riski Eka Yuliani; Dedi Hariyanto; Neni Triana Maswardi (Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study is to determine the effect of marketing mix on consumer decisions to buy two-wheeled vehicles Yamaha brand in PD. Turbo Motor Pontianak. The method used in this research is descriptive. Sampling technique using purposive sampling method, the sample used amounted to 100 respondents.The result of research based on simple linear regression analysis with regression equation Ŷ = 1,210 + 0,737X stated that every increase of one unit value from marketing mix variable, then value of purchasing decision increase 0,737. The results of research based on the correlation coefficient (R) of 0.690 means there is a strong relationship between the marketing mix with the purchase decision. While the results of research based on the coefficient of determination (R2) of 0.476 means the influence of marketing mix of purchasing decisions amounted to 47.6% and the remaining 52.4% influenced by other factors not examined in this study. While the feasibility test model (Test F) states that a simple linear regression model can be used to predict purchasing decisions that are influenced by the marketing mix with a value of F arithmetic 88.947 greater than the value of F table 3.94 or 88.947> 3.94. Thus it can be concluded that marketing mix variables have a significant effect on purchasing decisions.